Evaluation of quality indicators of cervical cytopathology tests carried out in a municipality of Paraná, Brazil - Juliana Cristina Magalhães; Leonarda S. F. Morais; Jacqueline Plewka; Maurício Turkiewicz; Rita G. Amaral
ABSTRACT Introduction: Although the criteria and recommendations are well defined to improve the quality of cervical cytopathology tests (Pap smear) in Brazil, the quality indicators of several laboratories are below the recommended standards. Objective: To evaluate the quality indicators of cervical cytopathology tests carried out by the Brazilian Unified Health System [Sistema Único de Saúde (SUS)]. Method: Cross-sectional study based on the results of cervical cytopathology tests conducted in the municipality of Cascavel, Paraná, Brazil, from January 2012 to December 2018. The study included 141,191 tests and the following variables were analyzed: sample suitability, cervical cytopathology tests result, and internal quality monitoring indicators recommended by the Brazilian Ministry of Health. Results: The percentage of unsatisfactory tests did not exceed 0.97%. The representation of the squamocolumnar junction ranged from 63% to 67.4%. The percentage of altered exams among the satisfactory samples ranged from 0.46% to 6.44%. The positivity index ranged from 0.46% to 6.44%, while the high-grade squamous intraepithelial lesion/satisfactory indicator ranged from 0.21% to 1.06%, atypical squamous cells of undetermined significance/altered ranged from 22.47% to 49.93%, atypical squamous cells of undetermined significance/satisfactory ranged from 0.1% to 2.57%: and atypical squamous cells of undetermined significance/squamous intraepithelial lesions ranged from 0.31 to 1.02. Conclusion: In 2012 and 2013, the high-grade squamous intraepithelial lesion/satisfactory and the positivity index indicators were below the recommended parameters, and in the remaining years, these indicators were within the parameters recommended. Consequently, a greater number of truly cancer precursor lesions were identified, demonstrating the importance of internal quality control in the prevention of cervical cancer.